Assessment of Technical Efficiency of Inbred HYV and Hybrid Rice Cultivation at Farm Level (Bangladesh Journal of Agricultural Research, 2012)
This study is very important in the present perspective of rice economy as  comparative economics of inbred HYVs and hybrid rice production was very  scanty. As such, the present study was conducted to examine the relative  productivity, profitability, and comparative technical efficiency of inbred HYVs  and hybrid rice production in some selected areas of Gazipur district. The study  was conducted in four villages in Sadar Upzila under Gazipur district, namely  Kesurita, Martarchar, Harinal, and Samantapur. A total of 80 farmers from the  four villages were interviewed consisting of 40 farmers for hybrid and 40 for  inbred HYVs rice. Data were generated by personal interview using structured  questionnaire through conducting farm level survey. The analysis revealed  that there was no significant difference between farmers practices and  recommended rate of hybrid seed, TSP, and MP. But the farmers used  urea and seed of inbred HYVs significantly higher than recommend  rate. Hybrid farms incurred total cost of Tk. 63377/ha and inbred farms  incurred Tk. 61195/ha, respectively. Net returns obtained from hybrid rice was  Tk. 59,056/ha whereas it was Tk. 42,818/ha for inbred HYVs rice. Average net  return of inbred rice was 38% lower compared to that of hybrid rice.  Benefit cost ratio of inbred and hybrid production was estimated to be  1.93 and 1.70, respectively. The average yield of inbred HYV was 6.03 t/ha and  by product was 4.50 t/ha, while those of hybrid were 7.76 t/ha and 5.50 t/ha,  respectively. The estimates of technical inefficiency implied that education,  farming experience, extension contact, land type, seedling age, and number of  seedlings per hill were the major determinants of inefficiency for both inbred  and hybrid rice growers. The mean technical efficiency was about 80% for  inbred and 86% for hybrid rice producers, respectively, indicating hybrid rice  growers were technically more efficient than inbred growers. Higher-level of  education and more contact with extension agents were found to contribute in  reducing technical inefficiency of both inbred and hybrid rice producers.  Although, inbred and hybrid rice producers faced some problems, but it was  more severe for hybrid DOI: http://dx.doi.org/10.3329/bjar.v37i2.11225 Bangladesh J. Agril. Res. 37(2): 235-250, June 2012